Physical Effort Exertion for Peer Feedback Reveals Evolving Social Motivations From Adolescence to Young Adulthood. (January 2023) - Rodman, Alexandra M.; Powers, Katherine E.; Kastman, Erik K.; Kabotyanski, Katherine E.; Stark, Abigail M.; Mair, Patrick; Somerville, Leah H.
Peer relationships and social belonging are particularly important during adolescence. Using a willingness-to-work paradigm to quantify incentive motivation, we examined whether evaluative information holds unique value for adolescents. Participants ( N = 102; 12–23 years old) rated peers, predicted how peers rated them, and exerted physical effort to view each peer's rating. We measured grip force, speed, and opt-out behavior to examine the motivational value of peer feedback, relative to money in a control condition, and to assess how peer desirability and participants' expectations modulated motivated effort across age. Overall, when compared with adolescents, adults were relatively less motivated for feedback than money. Whereas adults exerted less force and speed for feedback when expecting rejection, adolescents exerted greater force and speed when expecting to be more strongly liked or disliked. These findings suggest that the transition into adulthood is accompanied by a self-protective focus, whereas adolescents are motivated to consume highly informative feedback, even if negative.